Development of IoT-Based Accounting System for Automatic Environmental Data Monitoring - Susanti, Wilda; Renaldo, Nicholas; Chandra, Teddy; Tendra, Gusrio; Veronica, Kristy; Ramadhani, Ramadhani; Ramdani, Ramdani; Panjaitan, Harry Patuan; Junaedi, Achmad Tavip; Purnama, Intan (Interconnection: An Economic Perspective Horizon, 2024)
This study aims to develop an IoT-based accounting system called Smart Eco Ledger to automatically monitor and record environmental data for use in environmental accounting reports. The system integrates sensors (e.g., temperature, humidity, CO₂), a microcontroller (ESP32), cloud storage (Firebase), and a user-friendly web dashboard. It enables real-time monitoring, automatic data logging, and simple report generation for environmental performance tracking. The results showed that the system works accurately, with high user satisfaction scores in usability testing. This innovation bridges the gap between environmental monitoring and accounting practices by eliminating manual input and increasing data reliability. The novelty of this research lies in the integration of IoT technology with environmental accounting in real-time, supported by cloud systems and interfaces accessible to accounting professionals. Although testing was limited to indoor conditions and a small sample size, the system shows potential for wider adoption. Future research may include sensor expansion, blockchain integration, mobile access, and AI-based forecasting. The Smart Eco Ledger contributes to sustainable accounting practices and demonstrates a practical solution for organizations committed to environmental responsibility and digital transformation.